Routine Ultrasound at 30th–33rd weeks versus 30th–33rd and 35th–37th weeks in Low-Risk Pregnancies - Policiano, Catarina (2023)
Policiano, C., Mendes, J. M., Fonseca, A., Barros, J., Vargas, S., Cal, M., Martins, I., Carvalho, C., Martins, D., Clode, N., & Graca, L. M. (2023). Routine Ultrasound at 30th–33rd weeks versus 30th–33rd and 35th–37th weeks in Low-Risk Pregnancies: A Randomized Trial. Fetal Diagnosis and Therapy , 49(9-10), 425–433. https://doi.org/10.1159/000527112 --- Funding Information: This work was supported by a Research Grant from Fundação para a Ciência e Tecnologia (FCT)-SFRH/SINTD/92997/2013. The funder was not involved in the study design, collection, analysis, data interpretation, or in the writing of this report. The trial was registered in ClinicalTrials.gov with the identification number: NCT03200665.